Pengaruh Debt To Equity Ratio, Sales Growth, Total Asset Turnover, Return On Equity Terhadap Return Saham Perusahaan Consumer Goods - Pinuji Kukuh Herwinanto; Tuti Andjarsari (BIP's JURNAL BISNIS PERSPEKTIF, 2015)
The purpose of this research is to test empirically the effect of Debt to Equity Ratio, Sales Growth, Total Asset Turnover, Return on Equity to Stock Return in Consumer Goods Companies listed in BEI on 2010-2112. The formulation of the problem is hypothesized mainly on the basis of references and empirical study. The hypothesis are then examined by using the Multiple Linear Regression. T test and F test is used to test the influence significances of independent variables partially and simultaneously to stock return. The total population of this study is 36 companies. After doing the purposive sampling, there are 22 companies which is representative as the sample research. The finding of the research shows that Debt to Equiy Ratio, Sales Growth, Total Asset Turnover, and Return On Equity impact significantly to stock return, while the result of partial test shows that Sales Growth and Return On Equity impact positively and significant. Debt to Equity Ratio impacts positively and unsignificant and Total Asset Turnover impact negatively unsignificant to stock return.